Electrodynamics of Relativistic Particles Through Non-Standard Lagrangian (Journal of Atomic and Molecular Sciences, 2014)
The main aim of this paper is to discuss the electrodynamics of relativisticdynamics of particles bases on the notion of the non-standard Lagrangians whichhave gained increasing importance in the theory of nonlinear differential equations,dissipative dynamical systems and theoretical physics. The mathematical settings areconstructed starting from the modified Euler-Lagrange equation and modified Hamiltonsequations. Some illustrative examples are considered and discussed.
Keywords: non-standard Lagrangians; modified relativistic electrodynamics; modified Hamiltonian.